Pengembangan Media Sidarman (Sistem Peredaran Darah Manusia) pada Pembelajaran IPA Kelas V Sekolah Dasar - Rochmiyatun, Vera; Prayogo, Muhammad Suwignyo (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This study aims to develop Siderman media (human circulatory system) in class V elementary school science learning. Because there are still many students whose grades are below the KKM or there are still many students who do not understand science lessons, especially the material for the human circulatory system, several problems are found such as a lack of student motivation in learning, student emotions are less controlled so the learning process is not conducive. In addition to these problems, the method used by the teacher when teaching is the lecture method and students study with textbooks only so that students feel bored and bored and as a result students are more engrossed in their own world, for example playing alone or even chatting with their classmates resulting in low student learning outcomes. under KKM, especially material for the circulatory system for class V science subjects. Therefore the researchers developed the SIDERMAN media (Human Circulatory System) with the subject matter of the human circulatory system in natural sciences. This learning media aims to increase students' knowledge about the human circulatory system material in science class V so that this media is packaged attractively and is easy to use. Siderman media in science subjects is structured in an interesting way so that it is very suitable to be applied to science subjects, especially the human circulatory system for class V SD.